Feiyiliu mixture promotes non-small cell lung cancer cells apoptosis via inhibits ZDHHC18-mediated AKT1 phosphorylation - Yuxia Liu; Liang Ding; Shitao Li; Lisha Li; Daijun Xing; Xin Zheng; Baochen Zhou (Heliyon)
Protein post-translational modification (PTM) is a molecular switch that determines protein diversification and regulates cellular functions, affecting proteins' subcellular localization and three-dimensional structure. Protein palmitoylation is one of the PTMs closely related to tumorigenesis and tumor progression. Feiyiliu Mixture (FYLM) is an effective herbal prescription in clinical for the treatment of non-small cell lung cancers (NSCLC). It inhibits the expression of AKT and its phosphorylation through multiple mechanisms. However, the activation of protein phosphorylation is closely related to protein translocation mediated by palmitoylation. It is still necessary to investigate whether FYLM induces the palmitoylation of AKT and its underlying mechanism. In the present study, we explored the components and targets of FYLM and found that ZDHHC18 could bind to AKT1. Meanwhile, FYLM reduced ZDHHC18 protein expression (A549, p = 0.0215; H1299, p = 0.0008) and inhibited the activation of AKT1 phosphorylation (A549, p = 0.0002; H1299, p = 0.0003), leading to 30.3 % A549 and 31.3 % H1299 cells apoptosis. Nevertheless, ZDHHC18 is a member of the zinc finger DHHC domain-containing protein family, which mediates the interaction between proteins and membranes to regulate protein palmitoylation. Our study suggests a novel potential mechanism: FYLM suppresses AKT1 phosphorylation to treat NSCLC, which might be associated with ZDHHC18-regulated palmitoylation.